If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -6x = 6 + -7x Solving 14 + -6x = 6 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 14 + -6x + 7x = 6 + -7x + 7x Combine like terms: -6x + 7x = 1x 14 + 1x = 6 + -7x + 7x Combine like terms: -7x + 7x = 0 14 + 1x = 6 + 0 14 + 1x = 6 Add '-14' to each side of the equation. 14 + -14 + 1x = 6 + -14 Combine like terms: 14 + -14 = 0 0 + 1x = 6 + -14 1x = 6 + -14 Combine like terms: 6 + -14 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 4x+6=-57-5x | | 10(s-5)=-95 | | 19232=10a+108b | | 4+12x=-62+x | | (2x-5)+x=(8x+20)+32 | | y^6-3y^3-2=0 | | 4(x-1)=3x+2 | | -4x+32=-24+-18x | | B+2B=6-2B | | 60v=800m-1800a | | 1200m=5400a+60v | | (6x+9)(7x^2+8x+5)= | | -3(4p-6)=54 | | 5x-1=-1+5x | | x^3+18x-18=0 | | 78+7x=81+4x | | (2x-5)+8=(8x+20)+32 | | 125a^3+216a=0 | | f(x)=2x^2-12x+5 | | 5y+1=-26 | | 13-5n=2-7n+1 | | -7+3b=b+7 | | 15x-12y= | | 4x-5+1x=16x+20+1 | | 16a^2-2a+8=0 | | u-3v=5 | | 9x(x)-6=o | | u=3v+5 | | 2m+8=6m | | -9+2n=-1+2n | | 3y+1=7y+9 | | -13+2v+8v=8v-5 |